Chris Argyris: theories of action, double-loop learning and organizational learning - and Smith, Mark K. (The encyclopedia of pedagogy and informal education, 2013)
Chris Argyris: theories of action, double-loop learning and organizational learning. The work of Chris Argyris (1923-2013) has influenced thinking about the relationship of people and organizations…